ALGEBRAIC EQUATIONS. THEORY, METHODS, ALGORITHMS SOLUTIONS - T. R. Suyarov (Лучшие интеллектуальные исследования, 2024)
Abstracts. In the proposed work, practically all questions related to the theory of algebraic and irrational equations and methods of their analytical solution are presented from a unified position. The main attention is paid to algorithmic methods of solving the presented problems, so that it is possible to perform the necessary calculations in practice. Each chapter ends with typical tasks that take place in the entrance tests, GIA, USE and olympiads of various levels. Each chapter ends with typical problems occurring at entrance examinations, GIA, USE and Olympiads of various levels. By These tasks can be conditionally divided into three levels.